Expanding the versatility of aminoquinoline organometallic complexes as anticancer and antibacterial agents - Zinman, Paige (Department of Chemistry, 2024)
Cancer is a devastating non-communicable disease which continues to increase its burden on countries globally. Despite the numerous research and clinical breakthroughs, its prevention is one of the most significant health challenges of the 21st century. Chemotherapy is amongst the most common and effective methods for cancer treatment, however the severe side-effects and acquired chemo-drug resistance by numerous cancers has significantly hindered the efficacy of current chemotherapeutic drugs. Following the limitations of cisplatin and its platinum(II) derivatives, research has focused on the development of chemotherapeutic agents that incorporate alternative platinum-group metals (PGMs). The compelling need for novel treatment modalities has yielded the emergence of photodynamic therapy (PDT) for the treatment of various cancer types, bacterial infections as well as other human ailments. Increasing attention has been given to the development of metal complexes as photosensitisers based on their attractive photophysical and biological properties. The aminoquinoline motif has been recognised as a remarkably versatile pharmacophore owing to its paramount contribution in the clinical success of the historical antimalarial drug, chloroquine. On account of its inherent and ubiquitous biological activity the aminoquinoline structure is represented in numerous clinical drug agents today. This study focused on the synthesis of two series of aminoquinoline-based organometallic complexes comprising of various PGMs (Ir(III), Rh(III) and Ru(II)) as well as the transition metal Re(I). Rhenium is underexplored and highly underestimated for its potentially beneficial application in both therapeutic and diagnostic medical endeavours. With this in mind, the first series consisted of a 4-aminoquinoline-1,3,5-triazine trimeric ligand and the corresponding trihomonuclear Ru(II), Ir(III) and Rh(III) complexes. The second series of 4-aminoquinoline Schiff base ligands, bearing either a pyridyl or quinolyl entity, were subjected to metal complexation yielding mononuclear N,N-chelated Ru(II), Ir(III) and Re(I) organometallic complexes. The synthesized compounds were fully characterised by utilizing assorted spectroscopic (solution-state 1H, 13C{1H}, 2D NMR and solid-state 1H, CP-MAS 13C NMR, FT-IR spectroscopy) and analytical (melting point analysis, mass spectrometry and elemental analysis) techniques. Single crystal X-ray diffraction was also used to validate the proposed molecular structures. Due to the poor solubility in water and most polar solvents coupled with solution instability in coordinating solvents such as DMSO, the trinuclear complexes of Series 1 were not considered for further in vitro biological assessments. However, the compounds of Series 2 were evaluated, in the dark, for in vitro cytotoxicity against the hormone-dependent MCF-7 and hormone-independent triple negative MDA-MB-231 breast cancer cell lines. The results revealed that the Re(I) tricarbonyl complexes show the most promising activity with IC50 values ranging between 8.55 – 6.82 µM. These complexes were up to three times more active than cisplatin in both breast cancer cell lines. The photostable Ru(II) and Ir(III) polypyridyl complexes were investigated for their eligibility as PDT agents. Conducting in vitro cytotoxicity screenings against the 501 melanoma cancer cell line in the dark and in the light, confirmed that all complexes showed enhanced activity upon visible light irradiation at 455 nm. Across all three cancer cell lines the quinolyl-substituted complexes consistently showed superior activity compared to the pyridyl-substituted ones. This observation emphasizes the significance of the quinoline pharmacophore for anticancer drug design. In addition, the minimum inhibitory concentrations (MIC) of the ligands and Re(I) complexes of Series 2 were evaluated against two bacterial strains namely, methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli. All the tested compounds displayed selectivity towards the Gram-positive strain over the Gram-negative bacterial strain. The rhenium tricarbonyl complexes showed enhanced activity compared to the ligands against the MRSA bacterial strain, with the quinolyl-substituted Re(I) analogue displaying the best activity (MIC 12.5 – 25 µM).